2018
DOI: 10.1177/2399202618816900
|View full text |Cite
|
Sign up to set email alerts
|

Compliance to current national medicines law for proper storage and dispensing of medicines at community pharmacies in Bhutan

Abstract: Introduction: Compliance of community pharmacies with the national medicines law for proper storage and dispensing of medicines is crucial for ensuring the quality and safety of medicines. Community pharmacies in Bhutan are of two types: retail pharmacies and wholesale pharmacies. Objective: This study was aimed to assess the compliance of community pharmacies with the Medicines Act of the Kingdom of Bhutan 2003 and Bhutan Medicines Rules and Regulation 2012. Methods: This is a retrospective cross-sectional st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…25 Most of our study facilities had a majority of storage and dispensing facilities, which were in line with a study done in Bhutan that showed the compliance level of community pharmacies with the regulatory requirements for proper storing and dispensing of medicine was 90.4% for the regulatory provisions classified as critical, while it was 86.74% for the major category. 26 The findings from this finding suggest that pharmacies generally had a good availability of facilities for adhering to regulatory requirements for the proper storage and dispensing of medicines. Continued monitoring, training, and support for pharmacies can help maintain and improve compliance levels to ensure full facility availability, ultimately benefiting patient care and public health.…”
Section: Discussionmentioning
confidence: 86%
“…25 Most of our study facilities had a majority of storage and dispensing facilities, which were in line with a study done in Bhutan that showed the compliance level of community pharmacies with the regulatory requirements for proper storing and dispensing of medicine was 90.4% for the regulatory provisions classified as critical, while it was 86.74% for the major category. 26 The findings from this finding suggest that pharmacies generally had a good availability of facilities for adhering to regulatory requirements for the proper storage and dispensing of medicines. Continued monitoring, training, and support for pharmacies can help maintain and improve compliance levels to ensure full facility availability, ultimately benefiting patient care and public health.…”
Section: Discussionmentioning
confidence: 86%
“…surveys, questionnaires, interviews), and of those, 12,14–18,20–25 three also included observational inspections/visits 14,18,24 . In one study, Principal Investigator–administered inspections were used, 26 and in two, retroactive analyses of inspection data or a quantitative dataset were conducted 13,19 . The sample size of outlets for each study ranged from 38 to 1175, with a median sample size of 102 outlets and an average sample size of 128 outlets (standard deviation of 95) for all studies.…”
Section: Resultsmentioning
confidence: 99%
“…Notre étude a montré que les officines disposaient des auxiliaires/vendeurs et tous sont affectés à la délivrance des médicaments. Globalement, dans les pays en développement, la situation des ressources humaines à l'officine contraste avec celle des pays développés comme le Bhutan où près de 94% du personnel exerçant à l'officine ont la qualification requise [ 6 ].…”
Section: Discussionunclassified